1997
DOI: 10.1523/jneurosci.17-02-00516.1997
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Neuronal Remodeling Is Impaired in Patients with Alzheimer’s Disease Carrying Apolipoprotein ε4 Allele

Abstract: A relationship between the apolipoprotein E (apoE) genotype and the risk to develop Alzheimer's disease has been established recently. Apolipoprotein synthesis is implicated in developmental processes and in neuronal repair of the adult nervous system.In the present study, we investigated the influence of the apolipoprotein polymorphism on the severity of neuronal degeneration and the extent of plastic dendritic remodeling in Alzheimer's disease. Changes in length and arborization of dendrites of Golgi-impregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
176
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(190 citation statements)
references
References 111 publications
(116 reference statements)
10
176
0
4
Order By: Relevance
“…Furthermore, despite a 60% loss of AchE-positive neurons in the basal forebrain, ChAT activity in the hippocampus and cortex of e4 noncarrier AD subjects was relatively similar to that of e4 noncarrier controls. Similar results were reported by Arendt et al (1997). In a post-mortem study of nondemented subjects, Allen et al (1997) showed significantly greater reductions in ChAT activity in the temporal cortex of e4 carriers compared to e4 noncarriers.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, despite a 60% loss of AchE-positive neurons in the basal forebrain, ChAT activity in the hippocampus and cortex of e4 noncarrier AD subjects was relatively similar to that of e4 noncarrier controls. Similar results were reported by Arendt et al (1997). In a post-mortem study of nondemented subjects, Allen et al (1997) showed significantly greater reductions in ChAT activity in the temporal cortex of e4 carriers compared to e4 noncarriers.…”
Section: Introductionsupporting
confidence: 82%
“…Post-mortem brain tissue samples from AD patients who are e4 carriers have shown greater reductions in choline acetyltranferase (ChAT) activity, a cholinergic marker enzyme, in the hippocampus (Poirier, 1994;Allen et al, 1997), temporal cortex and nucleus basalis of Meynert (NBM) (Arendt et al, 1997), and the frontal cortex (Soininen et al, 1995). Other reports have also pointed to greater reductions in ChAT activity in AD patients homozygous for the e4 allele (e4/e4) in the hippocampus (Poirier, 1994) and the frontal cortex (Soininen et al, 1995) than AD patients who were heterozygous (ie e4/e3 or e4/e2).…”
Section: Introductionmentioning
confidence: 99%
“…12 The abnormalities of the neuronal dendrites and their synaptic spines reported in neurological cretinism bear a striking resemblance to those reported in Alzheimer's disease especially among APOE ⑀4 carriers. 13 Similar changes are reported in APOE knockout mice, and also when the human ApoE ⑀4 transgene is introduced into APOE null mice. 14 ApoE has a thyroid hormone (T4) binding domain, and may be involved in transport of T4 into cells.…”
Section: Introductionsupporting
confidence: 54%
“…Autopsies of human fetal brain from iodine-deficient areas are desirable but difficult to organize. It will be interesting to determine whether fetal iodine deficiency has a disproportionate effect upon the behavioral and neurological phenotype in strains of APOE null mice, 13 or mice where a human ⑀4 transgene has been introduced. 14 Neuropathological studies on these mice may also demonstrate increased abnormalities of neuronal differentiation and dendrite branching resembling endemic cretinism.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE is also involved in the response to neural injury (43,58,59), maintenance of dendritic arborizations (60), and neuronal remodeling in vitro (61,62) and in AD (63). The recent association of different polymorphisms in the promoter region with AD (32-35) strongly suggests that transcriptional regulation of APOE gene may play an important role in the development of this deleterious disease.…”
Section: Discussionmentioning
confidence: 99%